Gender Recognition Using a Min-Max Modular Support Vector Machine - Lian, Hui-Cheng; Lu, Bao-Liang; Takikawa, Erina; Hosoi, Satoshi (Advances in Natural Computation, 2005)
Considering the fast respond and high generalization accuracy of the min-max modular support vector machine (M3-SVM), we apply M3-SVM to solving the gender recognition problem and propose a novel task decomposition method in this paper. Firstly, we extract features from the face images by using a facial point detection and Gabor wavelet transform method. Then we divide the training data set into several subsets with the ‘part-versus-part’ task decomposition method. The most important advantage of the proposed task decomposition method over existing random method is that the explicit prior knowledge about ages contained in the face images is used in task decomposition. We perform simulations on a real-world gender data set and compare the performance of the traditional SVMs and that of M3-SVM with the proposed task decomposition method. The experimental results indicate that M3-SVM with our new method have better performance than traditional SVMs and M3-SVM with random task decomposition method.